2008
DOI: 10.1590/s0004-282x2008000600009
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and neuropsychological profile in a sample of children with attention deficit hyperactivity disorders

Abstract: -The aim of this study was to evaluate clinical and neuropsychological findings in children with suspicion of attention deficity hyperactivity disorder (ADHD). The assessment involved 150 children aged 7 to 14 referred to NANI at UNIFESP. Results: 75 children (55 M and 20 F) fulfilled the criteria for ADHD, among which 35 were of the inattentive type, 28 of combined type and 12 were hyperactive/impulsive. There was negative correlation between the digit score and the Corsi test. Children with hyperactivity and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
14
0
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 19 publications
2
14
0
1
Order By: Relevance
“…In relation to compulsive behaviors, there were fewer reports, although this type of behavior translates signs of anxiety and comorbidity is quite frequent in ADHD cases (17%), while specific complaints reported in this category were more related to behavior such as fidgeting with finger nails or skin (36). …”
Section: Discussionmentioning
confidence: 99%
“…In relation to compulsive behaviors, there were fewer reports, although this type of behavior translates signs of anxiety and comorbidity is quite frequent in ADHD cases (17%), while specific complaints reported in this category were more related to behavior such as fidgeting with finger nails or skin (36). …”
Section: Discussionmentioning
confidence: 99%
“…Using these norms, the performance of each child can be assessed in a more exact and standardized manner according to their age, gender, and the education of their parent(s). The creation of standardized norms will improve neuropsychological evaluation and diagnosis both in normal and clinical populations, since deficits are usually present in children with learning disabilities (Kirkwood, Weiler, Bernstein, Forbes, & Waber, 2001), brain injury (Verger et al, 2000), autism (Czermainski, Riesgo, Guimarães, Salles, & Bosa, 2014), and attention and hyperactivity disorder (Rizzutti et al, 2008), among others. Furthermore, norms to value the neuropsychological performance of children with impairments will inform their prognostic course and facilitate the implementation of cognitive rehabilitation programs among populations who may benefit.…”
Section: Discussionmentioning
confidence: 99%
“…Martín-González et al (2008), Robinson and Tripp (2013) and Rizzutti et al (2008) have shown that children without ADHD draw the initial design with a higher fidelity than children with ADHD, and in regards to visual memory performance, the studies of Bara-Jiménez et al (2003) and Robinson and Tripp (2013) have evidenced lower performance in children with ADHD. However, other studies did not find significant differences in the immediate recall phase (Filippetti & Mias, 2009;Martín-González et al, 2008).…”
Section: Estrategias De Organización En La Figura Compleja De Rey En mentioning
confidence: 99%